Rancangan “Wonderful Indonesia” Sebagai Branding-Destination - Dewi Kumoratih (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
The aim of this paper is to examine Indonesia’s latest branding-destination, “Wonderful Indonesia”. This study attemps to find the missing link between what the country is trying to communicate, represented by the logo of its destination brand, and how this logo is perceived by its audience. Furthermore, in conjunction with its campaign, it is also important to discover whether design as a discipline, plays a major role in the strategic planning of the nation’s grand-design. Required data of logo implementation and distribution were collected through online media as well as above the line and below the line media. The method used is based on qualitative research dan data was examined through art history, visual communication design dan marketing approaches. The outcome suggests that the Ministry responsible for tourism needs to re-evaluate its branding strategy in a more strategic basis due to its lack of consistency in terms of implementations and communications.